To Negotiate a Carbon Tax: A Rough Map of Interactions, Tradeoffs, and Risks - Gundlach, Justin (Columbia Journal of Environmental Law, 2019)
This Article assumes that the federal government will assign a price to carbon dioxide emissions via legislation by the early 2020s for one or more of myriad reasons. This Article’s purpose, however, is not to substantiate that assumption, but to explore a particular aspect of the adoption of such legislation. The contents of that legislation will reflect negotiated agreements—built on various political tradeoffs—over a host of policy issues, ranging from taxes to energy efficiency standards. These tradeoffs would implicate not only the tax’s scope and rate, but also the policies with which the tax would interact. This Article describes interactions between a carbon tax and various existing and proposed policies relating to climate change, energy, and environmental protection. It proceeds in five parts: Part II highlights three key points of background; Part III summarizes the universe of policies that can be expected to interact with a carbon tax; Part IV provides a rough typology of interactions among a carbon tax and other policies, labeling them Complementary, Concurrent, or Conflicting; Part V identifies several important potential tradeoffs; and Part VI, which is less descriptive and more prescriptive than the other four, highlights the risks of particular tradeoffs to the effectiveness of a climate change mitigation policy suite that includes a carbon tax. One thing this Article does not address is a discussion of the quantities of greenhouse gas (“GHG”) emissions that would likely be reduced by a carbon tax alongside or as a net result of combination with other policies—existing or otherwise. Such a discussion would be a useful line of further research but is beyond the scope of this Article. Why consider all of this now, in a political climate decidedly averse to addressing climate change at all? This Article takes as its basic premise that several circumstances create a real possibility that Congress could adopt a price on carbon, in the form of a tax, sometime around (most likely after) the 2020 presidential election: (i) a substantial number of Republican members of Congress and the Senate privately acknowledge the reality of anthropogenic climate change, and would support effective mitigation policy if doing so became less politically poisonous for them; (ii) Republicans’ control of Congress and the White House makes the present an opportune time to dismantle Obama-era regulatory responses to climate change, namely the Clean Power Plan and other regulations based on an interpretation of the Clean Air Act as requiring the Environmental Protection Agency to regulate GHG emissions; (iii) Democrats would bitterly oppose any Republican effort to undo all means of mitigating climate change by regulating GHG emissions and some Republicans would defect to join them; (iv) the Trump campaign promised a large program of infrastructure spending as well as income tax cuts, leaving open the question of how to secure new revenues to cover at least some of the promised spending; (v) Republicans’ complete control of Congress and the White House will not persist, and most Republican politicians recognize this; and thus, (vi) Republicans currently hold the strongest bargaining position they will have for the foreseeable future on the subject of federal climate change mitigation policy.